"Racism?!?. . . Just Look at Our Neighborhoods": Views on Racial Discrimination and Coping Among African American Men in Saint Louis. Issue 2 (June 2016) - Hudson, Darrell L.; Eaton, Jacob; Lewis, Porschea; Grant, Patrick; Sewell, Whitney; Gilbert, Keon
Recent events in Ferguson underscore the need to better understand the unique challenges, stressors, and coping mechanisms of African American men. To this end, a focus group study was conducted in Saint Louis, a few miles from Ferguson. Although numerous stress-related themes were discussed, racial discrimination and structural racism emerged as pervasive stressors among these men. Participants described experiences of discrimination in multiple settings including workplace, school, and residential, and within the criminal justice system. Coping strategies included not only drinking and smoking but also religiosity and familial support. Men also mentioned that they found relief in simply discussing their stressors in a group setting. One implication of this study is to develop and implement group support models for this population.